Non-Bonded Intermolecular Interactions and Crystal Stability of trans -1,4-Cyclohexanedicarboxylic Acid, 1,4-dibromo - Echeverría, Gustavo Alberto (2005)
Molecular geometry, crystal packing and thermal stability of trans-1,4-cyclohexanedicarboxylic acid, 1,4-dibromo (I) are examined, in order to analyse the relative influence of the different intermolecular interactions at play. From a comparison with the corresponding properties of trans1,4-cyclohexanedicarboxylic acid (II), some insights on the results of the competition between Br and carboxylic groups are obtained. In the crystalline state, the molecules of both compounds present chair centrosymmetric geometry and build infinite chains through ring hydrogen bonds involving the carboxylic groups. These groups are axial in I and equatorial in II, giving rise to different assembly of the chains. In both compounds there is in general good agreement between the in-crystal geometry and the B3LYP/LanL2DZ optimized geometry of the corresponding isolated molecule. The only significant differences are related to the carboxylic groups. The intermolecular contacts in I have been rationalized on the basis of a graph set analysis. A molecular dynamics based method has been used to analyse the temperature dependence of the mean life time of the different kinds of hydrogen bonds characterized in I. It has been found that the O–H⋅ ⋅O and C–H⋅ ⋅O(carbonyl) interactions are the main source of thermal stability. The melting point of I determined within this approach agrees very well with the experimental value.